‘Not feeling like a caged animal: ’ prisoner perceptions of a remote video visitation system - Murdoch, Danielle J. (Journal of crime and justice, 2020)
In recent years, correctional agencies have increased their use of video visitation in an effort to offset costs and increase security, among other objectives. In the present study, interviews (N = 12) and surveys (N = 58) were conducted with prisoners at a jail in the Northwestern U.S. that had replaced in-person, glass partition visitation with remote video visitation. The results suggested that while there were positive aspects of video visitation, such as the ability to visit with loved ones from afar, there were criticisms as well, including technological and access issues. The policy implications of the findings and directions for future research on video visitation are discussed.